(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Dela Peña WB, Ratilla BC. 2022. Assessment of pests, natural enemies and soil microorganisms in lowland rice fields under organic and inorganic production systems. Asian J Agric 6: 40-46. Farmers readily use synthetic pesticides over organic and natural pest management strategies in controlling pests that may disrupt the ecological balance. This study assessed the population of insect pests, natural enemies, and soil microorganisms associated with lowland rice PSB Rc18 grown under different production systems. A lowland area at the Department of Agronomy, Visayas State University, Visca, Baybay City, Leyte, Philippines, was used to produce organic rice for four consecutive croppings. Results revealed that organic farmers’ practice in Leyte (T2) showed a higher population of natural enemies, especially mirid bugs, fewer brown planthoppers, and green leafhoppers at 14-44 DAT and the number of folded leaves observed. However, conventional farmers’ practices in Leyte (T3) had the highest incidence and severity of bacterial blight and rice blasts. On the other hand, bacterial and fungal microorganisms were found to be associated with the soil samples. Furthermore, the fungal population increased in both organic production systems compared to the conventional production system. Hence, organic production systems increased the number of beneficial insects and soil microbes’ populations that may, directly and indirectly, affect pests and diseases in lowland rice.